Dynamics of machines and mechanisms, industrial research : selected, peer reviewed papers from the 2014 International Mechanical Engineering Congress (IMEC 2014), June 13-15, 2014, Tamil Nadu, India - Balasubramanian, K. R.; Sivapirakasam, S. P.; Anand, R. (Applied mechanics and materials ;, 2014)
Collection of selected, peer reviewed papers from the 2014 International Mechanical Engineering Congress (IMEC-2014), June 13-15, 2014, Tamil Nadu, India. The 501 papers are grouped as follows: Chapter 1: Advanced Material and Manufacturing Processes, Chapter 2: Nanomaterials and Nanotechnology in Machinery, Chapter 3: Dynamics and Applied Mechanics, Chapter 4: Tribology, Chapter 5: Thermodynamics and Thermal Engineering, Fuel and Diesel, Chapter 6: Applied Fluids Mechanics in Design of Machines and Equipment, Chapter 7: Vibration and Control, Chapter 8: Drive Systems of Machines, Mechatronics, Robotics and Control, Chapter 9: Engineering Development on Sustainable Energy, Chapter 10: Labour Safety, Ergonomics, Reliability and Safety of Machines and Mechanisms, Chapter 11: Industrial Engineering Keyword: Thermal Engineering, Dynamics, Vibration and Control, Industrial Engineering, Advanced Material and Manufacturing, Safety, Tribology, Micro-Electro-Mechanical-Systems, Sustainable Energy, Nano Technology and Fluid Systems Over 400 papers cover advanced material and manufacturing processes, nanomaterial and nanotechnology in machinery, dynamics and applied mechanics, tribology, thermodynamics and thermal engineering, fuel and diesel, applied fluid mechanics in the design of machines and equipment, vibration and control, drive systems of machines, mechatronics, robotics and control, the engineering development of sustainable energy, labor safety and ergonomics, the reliability and safety of machines and mechanisms, and industrial engineering. Among the topics are the effect of upset current when magnetically impelled arc butt welding carbon steel tubes, modeling and analyzing electrical discharge alloying through the Taguchi technique, the effect of shape imperfections on thin-walled pipe bends under out-of-plane moment and internal pressure, analyzing the stability of a flexible rotor supported by a plain circular bearing with micropolar fluid, and the effect of inlet air temperature on liquid fuel combustion in a taper can gas turbine combustion chamber. -- Engineering-- Mechanical engineering-- Robotics.